Methods for processing carbon materials
Patent Information
- Application Number
- JP2023136101
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-24
- Publication Date
- 2025-03-07
AI Technical Summary
【0008】 本開示によれば、炭素材料の特性を向上させることができる。
Smart Images

Figure 2025030626000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to methods for treating carbon materials. [Background technology]
[0002] Carbon materials such as carbon nanotubes and graphene are widely used (for example, see Patent Document 1). Treatments for improving the properties of carbon materials, such as their electrical conductivity, include oxidation-reduction by acid-base treatment, heat treatment, plasma treatment, and the like. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2017-222538 A Summary of the Invention [Problem to be solved by the invention]
[0004] According to oxidation-reduction by acid-base treatment, hydroxyl groups and the like can be introduced to the surface of the carbon material to improve electrical conductivity, but the crystallinity is not improved, so the improvement in electrical conductivity is limited. According to heat treatment, the carbon material can be graphitized to improve electrical conductivity, but the morphology of the carbon material changes. According to plasma treatment, functional groups can be introduced to the surface of the carbon material to improve electrical conductivity, but the crystallinity is not improved, so the improvement in electrical conductivity is limited.
[0005] The present inventors recognized the need to develop a new processing method for improving the properties of carbon materials, and arrived at the technique of the present disclosure.
[0006] The present disclosure has been made in view of these problems, and an object of the disclosure is to provide a treatment method for improving the properties of carbon materials. [Means for solving the problem]
[0007] In order to solve the above problems, a method for treating a carbon material according to one embodiment of the present invention includes the steps of placing a carbon material in a liquid containing a halogen atom-containing organic substance, and generating plasma in the liquid. Effect of the Invention
[0008] According to the present disclosure, the properties of carbon materials can be improved. [Brief description of the drawings]
[0009] [Figure 1] FIG. 2 is a diagram showing a schematic example of a missing portion of a carbon material. [Diagram 2] FIG. 2(a) is a TEM image of the single-walled carbon nanotube sample before treatment, and FIG. 2(b) is a TEM image of the single-walled carbon nanotube sample after treatment. [Diagram 3] FIG. 2 shows X-ray diffraction patterns of a single-walled carbon nanotube sample before and after treatment. [Figure 4] FIG. 2 shows electron spin resonance spectra of a single-walled carbon nanotube sample before and after treatment. [Diagram 5] FIG. 1 shows the carbon tetrachloride content dependence of electrical conductivity of single-walled carbon nanotube samples. [Figure 6] FIG. 13 is a diagram showing the solution plasma treatment time dependence of the electrical conductivity of a single-walled carbon nanotube sample. [Figure 7] FIG. 1 shows the carbon tetrachloride content dependence of electrical conductivity of multi-walled carbon nanotube samples. [Figure 8] FIG. 13 is a diagram showing the solution plasma treatment time dependence of the electrical conductivity of a multi-walled carbon nanotube sample. [Figure 9] FIG. 2 is a graph showing the dependence of electrical conductivity of graphite samples on the carbon tetrachloride content. [Figure 10] FIG. 13 is a diagram showing the solution plasma treatment time dependence of the electrical conductivity of a graphite sample. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Carbon materials made of carbon generally have portions where carbon atoms are missing. Figure 1 shows a schematic example of a missing portion of a carbon material. A carbon atom that should be at the position indicated by the dashed line is missing. Such a missing carbon atom can cause a deterioration in the properties of the carbon material.
[0011] The method for treating a carbon material disclosed herein comprises the steps of placing the carbon material in a liquid containing a halogen atom-containing organic substance, and generating plasma in the liquid.
[0012] For example, when a carbon material is plasma-treated in a liquid containing carbon tetrachloride (CCl4) and ethanol, the following reaction is thought to occur: CCl4 → CCl3 + Cl C2H5OH → C2 +5H +OH [ka] The carbon atoms derived from CCl4 fit into the defective parts of the carbon material, repairing the defective parts. This improves the electrical conductivity and other properties of the carbon material. It also improves the adhesion between carbon materials and expands the electrical contacts. The same applies when the halogen is F, Br, or I.
[0013] The carbon material may be graphene having a structure in which carbon atoms are bonded in a hexagonal lattice shape with a thickness of one atom, graphite having a layered structure in which graphene is stacked, single-walled carbon nanotubes (SWCNTs) in which one sheet of graphene is cylindrical, multi-walled carbon nanotubes (MWCNTs) in which single-walled carbon nanotubes are nested, cup-stacked carbon nanotubes having a structure in which cup-shaped carbon nanotubes are stacked, carbon nanofibers such as vapor-grown carbon fibers produced by vapor growth, carbon nanohorns in which graphene is conical, carbon nanobuds having a structure in which carbon nanotubes and fullerenes are bonded, diamond-like carbon (DLC) which is a thin film formed of a substance whose main component is carbon and which has both the carbon-carbon bonds of diamond and graphite, and fullerenes composed of a large number of carbon atoms in a closed-shell cavity shape.
[0014] The halogen atom-containing organic substance may be a haloalkane in which some or all of the hydrogen atoms of an alkane have been replaced with halogens, a haloalkene in which some or all of the hydrogen atoms of an alkene have been replaced with halogens, a haloalkyne in which some or all of the hydrogen atoms of an alkyne have been replaced with halogens, a haloarene in which some or all of the hydrogen atoms of an aromatic compound have been replaced with halogens, or a mixture containing any two or more of these. Haloalkanes include carbon tetrachloride (CCl4), carbon tetrafluoride (CF4), carbon tetrabromide (CBr4), carbon tetraiodide (CI4), chlorotrifluoromethane (CClF3), dichlorodifluoromethane (CCl2F2), trichlorofluoromethane (CCl3F), chloroform (CHCl3), fluoroform (CHF3), bromoform (CHBr3), iodoform (CHI3), chlorodifluoromethane (CHClF2), dichlorofluoro The haloalkene may be a halomethane such as methane (CHClF), dichloromethane (CHCl), difluoromethane (CHF), dibromomethane (CHBr), diiodomethane (CHI), chlorofluoromethane (CHClF), chloromethane (CHCl), fluoromethane (CHF), bromomethane (CHBr), iodomethane (CHI), or a mixture of any two or more of them. The haloalkene may be tetrachloroethylene (CCl), or the like. The haloarene may be chlorobenzene (CHCl), or the like.
[0015] The liquid may include an organic solvent, which may be an alcohol such as ethanol or methanol, hexane, benzene, chloroform, formic acid, acetic acid, ethyl acetate, diethyl ether, acetonitrile, acetone, dimethylsulfoxide, tetrahydrofuran, or the like.
[0016] The mixing ratio of the halogen atom-containing organic substance and the organic solvent may be 5:95 to 100:0. The content of the halogen atom-containing organic substance may be 5% or more, 10% or more, 15% or more, 20% or more, 25% or more, 30% or more, 35% or more, 40% or more, 45% or more, 50% or more, 55% or more, 60% or more, 65% or more, 70% or more, 75% or more, 80% or more, 85% or more, or 90% or more. The content of the halogen atom-containing organic substance may be 100% or less, 95% or less, 90% or less, 85% or less, 80% or less, 75% or less, 70% or less, 65% or less, 60% or less, 55% or less, 50% or less, 45% or less, 40% or less, 35% or less, 30% or less, 25% or less, 20% or less, 15% or less, or 10% or less.
[0017] The solution plasma treatment for generating plasma in a liquid includes a step of immersing electrodes in a liquid containing a carbon material and applying a pulse voltage between the electrodes to generate a glow discharge, thereby generating plasma in bubbles in the liquid. The pulse voltage may be 1000V or more, 1100V or more, 1200V or more, 1300V or more, 1400V or more, or 1500V or more. The pulse width of the pulse voltage may be 0.1μs or more, 0.2μs or more, 0.3μs or more, 0.4μs or more, 0.5μs or more, 0.6μs or more, 0.7μs or more, 0.8μs or more, 0.9μs or more, or 1.0μs or more. The pulse width of the pulse voltage may be 2.0 μs or less, 1.9 μs or less, 1.8 μs or less, 1.7 μs or less, 1.6 μs or less, 1.5 μs or less, 1.4 μs or less, 1.3 μs or less, 1.2 μs or less, 1.1 μs or less, or 1.0 μs or less. The frequency of the pulse voltage may be 1 kHz or more, 5 kHz or more, 10 kHz or more, 11 kHz or more, 12 kHz or more, 13 kHz or more, 14 kHz or more, 15 kHz or more, 16 kHz or more, 17 kHz or more, 18 kHz or more, 19 kHz or more, or 20 kHz or more. The frequency of the pulse voltage may be 40 kHz or less, 35 kHz or less, 30 kHz or less, 29 kHz or less, 28 kHz or less, 27 kHz or less, 26 kHz or less, 25 kHz or less, 24 kHz or less, 23 kHz or less, 22 kHz or less, 21 kHz or less, or 20 kHz or less. The time for performing the solution plasma treatment may be 1 minute or more, 5 minutes or more, 10 minutes or more, 15 minutes or more, 20 minutes or more, 25 minutes or more, or 30 minutes or more.The time for performing the solution plasma treatment may be 40 minutes or less, 35 minutes or less, 30 minutes or less, 25 minutes or less, 20 minutes or less, 15 minutes or less, 10 minutes or less, 5 minutes or less, or 1 minute or less.
[0018] Prior to the solution plasma treatment, the liquid containing the carbon material may be subjected to ultrasonic treatment.
[0019] As shown in the examples below, the intensity of the (101), (100), or (002) peak in the X-ray diffraction pattern of the carbon material after the treatment by the treatment method of the present disclosure is higher than that of the carbon material before the treatment. That is, the carbon material treated by the treatment method of the present disclosure has a higher crystallinity than the carbon material before the treatment. Due to this, the electrical conductivity of the carbon material after the treatment by the treatment method of the present disclosure is higher than that of the carbon material before the treatment.
[0020] [Example] A carbon material was treated by the treatment method of the present disclosure, and the properties of the carbon material before and after the treatment were compared.
[0021] [Sample preparation] In order to remove impurities from commercial single-walled carbon nanotubes (SWCNT), multi-walled carbon nanotubes (MWCNT), and graphite, they were heat-treated in air at 600°C for 4 hours. Next, in order to remove metal impurities, 200mL of 7M nitric acid was added to 200mg of carbon material, and the mixture was stirred at 100°C for 4 hours. Next, the mixture was washed and filtered using 0.1μm PTFE filter paper with 3L of deionized water. After that, the mixture was dried in air at 100°C for 24 hours. This was used as the sample before treatment.
[0022] [Solution plasma treatment] 170 mg of single-walled carbon nanotubes, 50 mg of multi-walled carbon nanotubes, and 200 mg of graphite were placed in a mixed liquid of 99.5% ethanol and carbon tetrachloride (carbon tetrachloride content of 5% to 70%) and ultrasonically treated for 5 minutes. After ultrasonic treatment, solution plasma treatment was started immediately. Solution plasma treatment was performed using 99.9% tungsten (W) electrodes with an electrode distance of 0.5 mm, a voltage of 1600 V, a pulse width of 1.0 μs, and a frequency of 20 kHz. When evaluating the carbon tetrachloride content dependency, solution plasma treatment was performed for 10 minutes in liquids with different carbon tetrachloride contents. When evaluating the solution plasma treatment time dependency, solution plasma treatment was performed for 5 to 30 minutes for single-walled carbon nanotube samples, 5 to 25 minutes for multi-walled carbon nanotube samples, and 1 to 6 minutes for graphite samples in a liquid with a carbon tetrachloride content of 30%. Next, the samples were washed with 1 L of ethanol and filtered using 0.1 μm PTFE filter paper. Thereafter, it was dried in air at 100° C. for 24 hours. This was used as the treated sample.
[0023] [Transmission electron microscope (TEM) image] 2(a) shows a TEM image of the single-walled carbon nanotube sample before treatment, and FIG. 2(b) shows a TEM image of the single-walled carbon nanotube sample after treatment, showing that the structure of the single-walled carbon nanotubes is not changed by the treatment method of the present disclosure.
[0024] [X-ray diffraction pattern] 3 shows the X-ray diffraction patterns of the single-walled carbon nanotube sample before and after the treatment. The intensity of the (002), (100), and (101) peaks in the X-ray diffraction pattern of the single-walled carbon nanotube sample after the treatment is higher than that of the single-walled carbon nanotube sample before the treatment. This indicates that the crystallinity of the carbon material is increased by the treatment method disclosed herein.
[0025] [Electron spin resonance (ESR) spectrum] 4 shows the electron spin resonance spectrum of the single-walled carbon nanotube sample before and after the treatment. The intensity of the peak due to the unpaired electrons in the defective portion in the single-walled carbon nanotube sample after the treatment is reduced compared to the single-walled carbon nanotube sample before the treatment. This indicates that at least a part of the defective portion of the carbon material was repaired by the treatment method of the present disclosure.
[0026] [Electrical conductivity] FIG. 5 shows the dependence of electrical conductivity of single-walled carbon nanotube samples on the carbon tetrachloride content. The electrical conductivity of the single-walled carbon nanotube sample before treatment is 220 S / m (dashed line in the figure). The electrical conductivity of the single-walled carbon nanotube sample that was subjected to solution plasma treatment in a liquid with a carbon tetrachloride content of 20 to 50% is higher than that of the untreated single-walled carbon nanotube sample. In particular, the electrical conductivity was maximum when the carbon tetrachloride content was 30%.
[0027] Figure 6 shows the solution plasma treatment time dependence of the electrical conductivity of single-walled carbon nanotube samples. The electrical conductivity of single-walled carbon nanotube samples treated with solution plasma for 5 to 15 minutes is higher than that of untreated single-walled carbon nanotube samples. In particular, the electrical conductivity was maximum when the solution plasma treatment was performed for 10 minutes.
[0028] From the above results, in the case of single-walled carbon nanotubes, the carbon tetrachloride content is preferably 20 to 50%, more preferably 25 to 40%. The time for solution plasma treatment is preferably 5 to 15 minutes. In particular, the electrical conductivity of the single-walled carbon nanotube sample that was subjected to solution plasma treatment for 10 minutes in a liquid of carbon tetrachloride:ethanol = 30:70 was 770 S / m, which was 3.5 times that of the untreated single-walled carbon nanotube sample.
[0029] Figure 7 shows the dependence of electrical conductivity of multi-walled carbon nanotube samples on the carbon tetrachloride content. The electrical conductivity of the multi-walled carbon nanotube sample before treatment is 26.9 S / m (dashed line in the figure). Because the time for solution plasma treatment was not optimal, the electrical conductivity of the treated multi-walled carbon nanotube sample is lower than that of the untreated multi-walled carbon nanotube sample. However, the electrical conductivity of the sample that was subjected to solution plasma treatment in a liquid with a carbon tetrachloride content of around 30% was shown to be high.
[0030] Figure 8 shows the solution plasma treatment time dependence of the electrical conductivity of multi-walled carbon nanotube samples. The electrical conductivity of multi-walled carbon nanotube samples treated with solution plasma for 15 to 25 minutes is higher than that of untreated multi-walled carbon nanotube samples. In particular, the electrical conductivity was maximum when the solution plasma treatment was performed for 20 minutes.
[0031] From the above results, in the case of multi-walled carbon nanotubes, the carbon tetrachloride content is preferably 20 to 50%, more preferably 25 to 40%. The time for solution plasma treatment is preferably 15 to 25 minutes. In particular, the electrical conductivity of the multi-walled carbon nanotube sample that was subjected to solution plasma treatment for 20 minutes in a liquid of carbon tetrachloride:ethanol = 30:70 was 32.7 S / m, which was 1.21 times that of the untreated multi-walled carbon nanotube sample.
[0032] Figure 9 shows the dependence of the electrical conductivity of the graphite sample on the carbon tetrachloride content. The electrical conductivity of the graphite sample before treatment is 52.3 S / m (dashed line in the figure). Because the time for solution plasma treatment was not optimal, the electrical conductivity of the treated graphite sample is lower than that of the untreated graphite sample. However, it was shown that the electrical conductivity of the graphite sample that was solution plasma treated in a liquid with a carbon tetrachloride content of around 10% was high.
[0033] Figure 10 shows the dependence of the electrical conductivity of the graphite sample on the solution plasma treatment time. The electrical conductivity of the graphite sample treated with solution plasma for 1 to 4 minutes is higher than that of the untreated graphite sample. In particular, the electrical conductivity was maximized when the solution plasma treatment was performed for 1 minute.
[0034] From the above results, in the case of graphite, the carbon tetrachloride content is preferably 5 to 20%, and more preferably 5 to 15%. The time for solution plasma treatment is preferably 1 to 4 minutes. In particular, the electrical conductivity of the graphite sample that was subjected to solution plasma treatment for 1 minute in a liquid of carbon tetrachloride:ethanol = 10:90 was 61.1 S / m, which was 1.17 times that of untreated graphite.
[0035] The present disclosure has been described above based on examples. These examples are merely illustrative, and it will be understood by those skilled in the art that various modifications are possible in the combination of each component and each treatment process, and that such modifications are also within the scope of the present disclosure.
Claims
1. Putting a carbon material into a liquid containing a halogen-containing organic substance; generating a plasma in the liquid; A method for treating a carbon material comprising:
2. The halogen-containing organic compound is a haloalkane, a haloalkene, a haloalkyne, a haloarene, or a mixture containing two or more of them. The method of claim 1.
3. The liquid comprises an organic solvent. The method according to any one of claims 1 to 2.
4. The organic solvent includes ethanol. The method of claim 3.
5. When the carbon material is carbon nanotubes, the content of the halogen-containing organic substance in the liquid is 20 to 50%. The method of claim 3.
6. When the carbon material is graphite, the content of the halogen-containing organic substance in the liquid is 5 to 20%. The method of claim 3.
7. The carbon material after the treatment has a higher crystallinity than the carbon material before the treatment. The processing method according to any one of claims 1 to 2.
8. The intensity of the (101), (100), or (002) peak in the X-ray diffraction pattern of the carbon material after the treatment is higher than that of the carbon material before the treatment. The processing method according to any one of claims 1 to 2.
9. The electrical conductivity of the carbon material after treatment is higher than that of the carbon material before treatment. The method according to any one of claims 1 to 2.
Citation Information
Patent Citations
Method for producing graphene and chemically modified graphene
JP2017222538A